The sedimentology, geochemistry and diagenesis of West Rand Group sediments in the Heidelberg area, Transvaal - Camden-Smith, P M (Department of Geological Sciences, 2016)
This study deals with the West Rand Group (formally the Lower Division of the Witwatersrand System) sediments within an area of approximately 500 km east of Heidelberg. The aim of the study was to interpret from the stratigraphy, lithology, petrology and sedimentary structures, the type of processes which were involved in the deposition of the arenaceous units of the West Rand Group, the current dispersal pattern and the probable, equivalent modern day depositional environment. The extent of diagenesis and metamorphism was investigated by using two white mica techniques. The chemistry of the shales was related to its mineralogy and a detailed study of the geochemical profile below the West Rand/Central Rand unconformity was undertaken. The West Rand Group east of Heidelberg is made up of a thick (3400 m) succession of alternating arenaceous and argillaceous units. It has traditionally been subdivided into three Subgroups - the Hospital Hill, Government and Jeppestown. Each Subgroup is divided into three formations on the basis of laterally persistent markers. Facies analysis has indicated that deposition occurred in the following environments in the different Formations: (1) the first shale horizon of the Orange Grove Quartzite Formation marks a change from "high" energy-wave dominated to lower energy - tide dominated conditions. The basal conglomerates and overlying trough crossbedded facies are interpreted as either platform beach or inlet deposits while ebb tidal deltas and local storm deposits characterise the rest of the arenaceous succession (2) the shales and thin sublitharenites of the Park- Town Shale Formation were formed by suspension deposition of mud alternating with periodic sand influxes while the banded iron formations and magnetite rich zones probably represent distal shelf muds. (3) the 'sago'-textured units of the Brixton Formation were deposited by storm ebb surge currents in conjunction with tidal currents (4) at the base of the Promise Quartzite Formation offshore (sub- tidal shelf) marine conditions prevailed. Nearshore sequences and finally a braided stream setting of the Platte type is interpreted for the rest of the succession (5) the poor outcrop of 'tillite' in the Coronation Shale Formation made it impossible to delineate the facies associated with the till (6) the immature subgreywackes of the Witpoortjie Formation below the Government Reef represent subtidal shelf and inshore tidal flat deposits. The Government Reef marker represents an ancient beach deposit with onshore migrating sandbars and ripples moving in response to shoaling waves. The Blue Grit marker is interpreted as either a fossil submarine rockfall or a cannon and fan valley deposit (7) the shales of the Jeppestown Subgroup represent proximal shelf deposits while the sandstones formed as a response to tidal, shelf and possibly fluvial processes. The Weber crystallinity index indicates that the mineral assemblage (white mica, chlorite and quartz) are low grade. The West Rand Group's Hb(rel) value of 150 corresponds to an approximate temperatures of 290°C. The study areas baric constraints are similar to the conditions for the Hercynian metamorphism in the eastern Alps. The relative amounts of clay mineral present in a sample was calculated from its bulk chemistry. Chlorite, illite and muscovite (in that order) are the major clay phases present. The trace element abundance indicates that the source rocks for the West Rand Group in the study area are similar in petrology to the source rocks of the Fig Tree sediments. The trace elements - Sr, Ni, Rb, ca, Zn, Cr - can be used to discriminate the shales of the West Rand, Central Rand and Fig Tree Groups. The Jeppestown shale immediately below the Main Conglarerate has a geochemical profile that has traits of a palaeosol which has subsequently been modified by diagenesis and the percolation of ground waters. Two models are proposed for the deposition of the Hospital Hill Subgroup and the Government Subgroup by integrating the writer's detailed facies analysis approach with the work done by previous workers in other outcrop areas.